Congenital Adrenal Hyperplasia Due to 21-Hydroxylase Deficiency: An Update on Genetic Analysis of CYP21A2 Gene - Carvalho, Berta; Marques, C. Joana; Santos-Silva, Rita; Fontoura, Manuel; Carvalho, Davide; Carvalho, Filipa (Experimental and Clinical Endocrinology & Diabetes, 2020)
Congenital Adrenal Hyperplasia is a group of genetic autosomal recessive disorders that affects adrenal steroidogenesis in the adrenal cortex. One of the most common defects associated with Congenital Adrenal Hyperplasia is the deficiency of 21-hydroxylase enzyme, responsible for the conversion of 17-hydroxyprogesterone to 11-deoxycortisol and progesterone to deoxycorticosterone. The impairment of cortisol and aldosterone production is directly related to the clinical form of the disease that ranges from classic or severe to non-classic or mild late onset. The deficiency of 21-hydroxylase enzyme results from pathogenic variants on CYP21A2 gene that, in the majority of the cases, compromise enzymatic activity and are strongly correlated with the clinical severity of the disease. Due to the exceptionally high homology and proximity between the gene and the pseudogene, more than 90% of pathogenic variants result from intergenic recombination. Around 75% are deleterious variants transferred from the pseudogene by gene conversion, during mitosis. About 20% are due to unequal crossing over during meiosis and lead to duplications or deletions on CYP21A2 gene. Molecular genetic analysis of CYP21A2 variants is of major importance for confirmation of clinical diagnosis, predicting prognosis and for an appropriate genetic counselling. In this review we will present an update on the genetic analysis of CYP21A2 gene variants in CAH patients performed in our department.
Keywords: Congenital adrenal hyperplasia; CYP21A2 gene; 21 hydroxylase; deficiency